Visual cues of motion that trigger animacy perception at birth: the case of self‐propulsion. Issue 4 (21st February 2016) - Di Giorgio, Elisa; Lunghi, Marco; Simion, Francesca; Vallortigara, Giorgio
Abstract: Self‐propelled motion is a powerful cue that conveys information that an object is animate. In this case, animate refers to an entity's capacity to initiate motion without an applied external force. Sensitivity to this motion cue is present in infants that are a few months old, but whether this sensitivity is experience‐dependent or is already present at birth is unknown. Here, we tested newborns to examine whether predispositions to process self‐produced motion cues underlying animacy perception were present soon after birth. We systematically manipulated the onset of motion by self‐propulsion (Experiment 1) and the change in trajectory direction in the presence or absence of direct contact with an external object (Experiments 2 and 3) to investigate how these motion cues determine preference in newborns. Overall, data demonstrated that, at least at birth, the self‐propelled onset of motion is a crucial visual cue that allowed newborns to differentiate between self‐ and non‐self‐propelled objects (Experiment 1) because when this cue was removed, newborns did not manifest any visual preference (Experiment 2), even if they were able to discriminate between the stimuli (Experiment 3). To our knowledge, this is the first study aimed at identifying sensitivity in human newborns to the most basic and rudimentary motion cues that reliably trigger perceptions of animacy in adults. Our findings are compatible with the hypothesis of the existence of inborn predispositions to visual cues of motion that trigger animacy perception in adults. Abstract : Understanding how humans identify and separate social agents from other objects and how this ability develops are open and intriguing questions. The aim of this paper was to investigate sensitivity in human newborns to the most basic and rudimentary motion cues that reliably trigger perception of animacy in adults. We sistematically manipulated the onset of motion by self‐propulsion (Exp.1) and the change in trajectory direction in the presence or absence of direct contact with an external object (Exp.2 and Exp.3) to investigate how these motion cues determine preference in newborns. Data demonstrated that, at least at birth, the self‐propelled onset motion is a crucial visual cue that allowed newborns to differentiate between self and non‐self‐propelled objects. Overall, our findings are compatible with the hypothesis of the existence of inborn predispositions to visual cues of motion that trigger animacy perception in adults.